87.1k views
2 votes
What is the solution to the equation -(5-(a+1))=9-(5-(2a-3))

User Darkiron
by
5.7k points

2 Answers

4 votes
Step 1: Simplify both sides of the equation.
−(5−(a+1))=9−(5−(2a−3))
−(5−(a+1))=9+−1(5−(2a−3))(Distribute the Negative Sign)−(5−(a+1))=9+(−1)(5)+−1(−2a)+(−1)(3)−(5−(a+1))=9+−5+2a+−3a+−4=9+−5+2a+−3(Distribute)a−4=(2a)+(9+−5+−3)(Combine Like Terms)a−4=2a+1a−4=2a+1Step 2: Subtract 2a from both sides.a−4−2a=2a+1−2a−a−4=1Step 3: Add 4 to both sides.−a−4+4=1+4−a=5Step 4: Divide both sides by -1.−a−1=5−1a=−5
User Anders Vestergaard
by
5.5k points
0 votes

Answer:

a)-5

Explanation:

-(5-(a+1))=9-(5-(2a-3))

= -(5-a-1)= 9-(5-2a+3)

= -5+a+1 = 9-5+2a-3

= -4+a = 1+2a

= -4 - 1 = 2a-a

= -5 = a

User Tinple
by
5.1k points